persaingan Analysis of the Effect of Perceived Product Quality, Price Feasibility and Brand Image on Customer Satisfaction: - Alifia Lintang Dharmanisa; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the effect of perceived product quality, price worthiness, and brand image to customer satisfaction at Mie Gacoan Tamansiswa. his type of research is descriptive with a quantitative approach. Research subjects are consumers who have purchased more than once products at Mie Gacoan Tamansiswa. Primary data obtained from a questionnaire with 154 respondents with purposive sampling. The results of the research on the test show that the Perceived Product Quality (X1) has positive and significant effect on Customer Satisfaction (Y) with a value of 0,000. The Price Worthiness (X2) has positive and significant effect on Customer Satisfaction (Y) with a value of 0,001. And the Brand Image (X3) has positive and significant effect on Customer Satisfaction (Y) with a value of 0,005. In the results of the F test Perceived Product Quality, Price Worthiness, Brand Image simultaneously affect to Customer Satisfaction which is indicated by a significance value of 0.000. Keyword: Perceived Product Quality, Price Worthiness, Brand Image, Customer Satisfaction.